PELATIHAN KOMUNIKASI PEMASARAN DIGITAL UNTUK MENINGKATKAN SEMANGAT WIRAUSAHA DI MASA PANDEMI COVID-19 - Dyanasari, Reni; Silvialestari, Dewi; Syifa Mutma, Fasya (Asosiasi Dosen PkM Indonesia, 2021)
The development of information and technology can help meet the needs of the community in seeking information. This can be utilized by businesses to make their products recognizable, accepted, and used by consumers. Utilizing social media and marketplaces is an effort that can be done by businesses to utilize digital technology in running their businesses. The Officer of Ruang Publik Terpadu Ramah Anak and the surrounding community already has a business run by groups and individuals engaged in food and fashion. So far, marketing activities conducted is to offer products to local residents who visit the area. Since the covid 19 pandemic, businesses feel the need for efforts to conduct digital marketing so that their business can still be run despite restrictions on physical activities of local residents or visitors who were targeted. But businesses need some tips to create digital marketing strategies utilizing social media and marketplaces. The community service team conducted an online seminar by delivering materials involving concepts in the context of Marketing Communication. Then, dissected first about the definition of online marketing communication, social media, ecommerce, and marketplace. In addition, seminar participants also get tips and tricks to produce content using simple tools but still attract potential consumers through social media and the marketplace. In the implementation of online seminars, participants were given pre-tests and post-tests to measure participants' understanding of the materials presented. After attending the seminar, the post-test results showed the seminar participants understood the material presented.